IMPROVING WRITING HABITS THROUGH COMPUTER ASSISTED MODELLING: AN EXPERIMENTAL STUDY WITH PRESCHOOLERS - Bornas, Xavier; Servera, Mateu; Llabrés, Jordi; Matas, Isabel (Anales de Psicología / Annals of Psychology, 2000)
The aim of this study is to assess the effectiveness of the VISPRO.Grafías application to improve letter writing in its initial steps. Writing quality (number of errors) was measured directly while preschoolers wrote ten different letters (n=27). The best writers were assigned to the control group (n=7). The other children were randomly assigned to the experimental groups A and B (n=10). Treatment consisted of ten individual sessions of ten minutes. During each session the child worked with the application in order to improve his or her letter writing. When the group A completed the intervention, the quality writing of all children was assessed again, and a third evaluation was carried out after intervening on the group B. Results show a statistically significant decrease of the number of errors made by children after treatment. Both groups A and B reach the same level than group C at the end of the program. Furthermore, treatment seems to be better than the daily writing work that children did in the classroom.